In Counterpoint : Diaspora, Postcoloniality, and Sacramental Theology. - Suna-Koro, Kristine (Eugene : Wipf and Stock Publishers, 2017)
What does postcoloniality have to do with sacramentality? How do diasporic lives and imaginaries shape the course of postcolonial sacramental theology? Neither postcolonial theorists nor sacramental theologians have hitherto sought to engage in a sustained dialogue with one another. In this trailblazing volume, Kristine Suna-Koro brings postcolonialism, diaspora discourse, and Christian sacramental theology into a mutually critical and constructive transdisciplinary conversation. Dialoguing with thinkers as diverse as Edward Said and Gayatri Spivak as well as Francis D'Sa, S.J., Martin Luther
Print version record.
Master record variable field(s) change: 072, 082
Keywords: Postcolonial theology; Sacraments -- History of doctrines; RELIGION / Christian Rituals & Practice / Worship & Liturgy; RELIGION / Institutions & Organizations; Electronic books